ANALISIS MASERAL DENGAN METODE REFLECTANCE VITRINITE UNTUK MENGETAHUI KUALITAS BATUBARA PADA SUMUR AL 25, LAPANGAN KINTAP, KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN, PT. ANUGERAH LUMBUNG ENERGI - Lutfi Hakim; Prakosa Rachwibowo; Dian Agus Widiarso; Bagus Zaqqie (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
The spread of coal deposits in Indonesia is quite large, most of coal basin is located in Sumatra and Kalimantan. One of the basin that produce economical coal deposit with value of calories more than 6.000 kal/g in Tanjung Formation is Asam-Asam Basin (Darlan etc, 1999). PT Anugerah Lumbung Energi is one of the coal mining companies with mining working area on Asam-asam basin. Research area is located in Kintap field, Tanah Laut Regency, South Kalimantan. The aim of this research is to find out about coal quality using maceral analysis with vitrinite reflectance method on well AL 25 and spread direction of coal seam at the research area.Methods of research are descriptive and analysis. Based on these methods, done the stage of the analysis and interpretation with data supporting are stratigraphical data and laboratory data. Activities performed such as geological mapping, maceral analysis with vitrinite reflectance methods and coal quality interpretation on well AL 25. The software used to support this undergraduate thesis are the Arcgis ,Autocad X 5 and Corel Draw. In Undergraduate Thesis, the author has divided into five phases, such as lithology description, cropline withdrawal based on strike and dip, maceral analysis, coal quality interpretation and results correlation of maceral analysis, rank and coal quality on the well AL 25.Based on the result of analysis data, it can be interpreted that lithology at the research area are sandstones, siltstone, claystone and thin layer of coal. The direction of seam coal ( cropline ) at the research area is southeast - northwest based on strike / dip. The results of the maceral analysis for each seam produce rank between Lignite to High Volatile bituminous B, whereas the results of the quality analysis for each seam produces a caloric value ranging from 12040.35 to 13786.69 Btu/lb or ranged from High Volatile Bituminous C to High Volatile Bituminous B. Based on the result of maceral analysis, rank and coal quality, it can be concluded that there are a mutual relation between maceral, rank and coal quality. The mutual relation is when the high percentage value of vitrinite reflectance so that value of coal calorie is good too.